Company Performance as Moderation the Effect of Leverage on Company Value - Putu Pande R. Aprilyani Dewi; Ni Putu Budiadnyani; I G A Desy Arlita (Syntax Idea)
The establishment of a company that applies economic concepts has the main goal of generating profits by optimizing the value of the company. Maximizing company value means realizing the stock market price, which means that if stock price movements increase constantly, it is able to explain the implementation of company goals This research uses quantitative research. The type of data used in this study is the type of secondary data obtained from the Indonesia Stock Exchange in 2019 – 2021. The population of this study is banking companies listed on the Indonesia Stock Exchange as many as 46 companies. Sampling of this study using purposive sampling then obtained a sample of 60 companiesResults, When the company's performance is good, the effect of leverage on company value can be positive. This occurs when leverage is used wisely and directed to enhance a company's growth, such as investments in research and development of new products, acquisitions of complementary companies, and development of new markets. If the company's performance is good, the effect of leverage on the value of the company can be positive because leverage can be used to increase the growth of the company. However, if a company's performance is poor, the effect of leverage on the company's value can be negative because leverage can increase the company's risk and uncertainty.